COST-PROFIT RELATIONSHIP IN CULTURAL PRACTICES AT SUGARCANE - Amorim, Fernando Rodrigues de [UNESP]; Solfa, Federico Del Giorgio; Queiroz, Timoteo Ramos [UNESP] (Fundacao Pedro Leopoldo, 2024)
Objective of the study: The objective of this work is to analyze the costs and profits of sugarcane production related to the cultural practices of sugarcane suppliers. Methodology / approach: This study is positioned in this gap when comparatively analyzing 6 types of cultural practices: delineation, swathing, application of corrective, herbicides, insecticides, and fertilizers, with the option of two systems Fixed Rate (TF) and Variable Rate (TV). Originality / Relevance: Brazil is a world reference in the production of sugarcane, and the State of Sao Paulo is the largest Brazilian producer. However, for sugarcane suppliers to remain in this activity, there is a need to reduce production costs and increase profitability/ha. However, there is a theoretical -practical gap in the financial evaluation (costs and profits) of different cultural practices inherent to the production of sugarcane. Main results: The results showed that the costs with cultural practices represent more than 30% of the total costs of sugar cane production. The TF system proved to be more cost-efficient, in the following operations: corrective, herbicides, and insecticides. In the application of fertilizers, the TV system, in the stretch mode, had the best result. Finally, profit/ton was R$ 1.70, showing a very low profit/ha margin because of the risk of the activity. Theoretical / methodological contributions: The sample of this research comprised 55 sugar cane suppliers, from the State of Sao Paulo, whose data were obtained through a survey. The comparative analysis was based on the difference in costs of cultural practices and the estimate of the level of certainty (profit/costs), analyzed through the cumulative frequency performed through the Monte Carlo Simulation (SMC).
Keywords: Monte Carlo Simulation; Fixed-Rate System; Variable Rate System